2000
DOI: 10.1128/aem.66.1.80-86.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Actions of Degraded and Native Chitosan against Spoilage Organisms in Laboratory Media and Foods

Abstract: The objective of this study was to determine whether chitosan (poly-␤-1,4-glucosamine) and hydrolysates of chitosan can be used as novel preservatives in foods. Chitosan was hydrolyzed by using oxidative-reductive degradation, crude papaya latex, and lysozyme. Mild hydrolysis of chitosan resulted in improved microbial inactivation in saline and greater inhibition of growth of several spoilage yeasts in laboratory media, but highly degraded products of chitosan exhibited no antimicrobial activity. In pasteurize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
201
0
22

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(227 citation statements)
references
References 14 publications
4
201
0
22
Order By: Relevance
“…Chitosan has shown to have inhibitory effect on growth of many plant pathogens [28,29]. This compound has shown properties, such as bioactivity and biocompatibility [30].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has shown to have inhibitory effect on growth of many plant pathogens [28,29]. This compound has shown properties, such as bioactivity and biocompatibility [30].…”
Section: Discussionmentioning
confidence: 99%
“…The most resistant strain, S. ludwigii, required 5 g/L of chitosan for complete inactivation and for maintaining yeast-free conditions in apple juice for 14 days at 25°C (Roller and Covill 1999). Another study by Rhoades and Roller (2000) showed that 0.3 g/L of Chitosan eliminated all the yeasts in pasteurized apple-elderflower juice during a 13-day of storage at 7°C. However, the total bacterial counts and the lactic acid bacterial counts increased slower than the control (Rhoades and Roller 2000 Chitosan has been approved as a food additive in Japan in 1983 and in Korea in 1995.…”
Section: Chitozanmentioning
confidence: 99%
“…A limited works have been done to assess the antimicrobial properties of chitosan in fruit juices (Roller and Covill 1999;Rhoades and Roller 2000). Chitosan glutamate was reported to be an effective preservative against spoilage yeasts in apple juice.…”
Section: Chitozanmentioning
confidence: 99%
“…Xanthan gum is not easily degraded by microorganisms (Cadmus et al, 1982), and chitosan polymers have antimicrobial activities. Interestingly, partially degraded chitosan demonstrates enhanced antimicrobial activities (Rhodes and Roller 2000). While biopolymer biodegradation is enhanced by elevated temperature and salt concentrations, metals sorbed to organic chelators can significantly decrease their rate of biodegradation (Francis and Dodge, 1993).…”
Section: Introductionmentioning
confidence: 99%